Can Sleep Quality Be the Intervening Factor of Personality Data to Occupational Fatigue? - David Kusmawan; M.Doddy Izhar; Fatma Lestari; Budi Aswin (Jurnal Kesehatan Masyarakat, 2026)
Fatigue during work among oil and gas employees can have dangerous effects on well-being, economics, safety, and health. This cross-sectional survey was conducted in July and August of 2022 at two national oil and gas companies located in Muara Jambi and Jambi City. A convenience sample of 116 respondents was selected in total. To address the study hypotheses, partial least squares-structured equation modelling (PLSSEM) was employed. This study aims to determine the relationship between the risk of job weariness among Indonesian oil and gas workers in Jambi Province and the direct and indirect impacts of mental workload, sociodemographic characteristics, and sleep quality. Personality data has a significant and negative direct impact on occupational weariness at alpha 5% and with a path value of -0.203 (p-value: 0.047), corroborating the earlier hypothesis. For the second hypothesis, the path coefficient value of 0.462 (p-value: 0.000) clearly shows that sleep quality has an impact on occupational weariness. In order to improve sleep hygiene and address personality factors like age and length of employment, fatigue risk management strategies can be combined with those that are currently being used to control job tiredness.